Digital Marketing Education of Jamu (Indonesian Traditional Herbal Medicine) for Students of State Junior High School 3 Tawangsari, Sukoharjo Regency as an Effort to Support Jamu Regenc - Priyono, Kuswaji Dwi; Danardono, D; Hadibasyir, Hamim Zaky; Ambarwati, A; Harismah, Kun (Journal of Community Services and Engagement: Voice of Community (VOC), 2022)
Sukoharjo Regency is known as the City of Herbal Medicine in Indonesia, since some of its residents work as sellers of traditional herbal medicine for generations in big cities. During the Covid-19 pandemic they had to return home, because of large scale social restriction that prohibits interaction between residents. While the Covid-19 pandemic outbreak demands a strong self-immunity, various types of traditional medicinal plants have increased in price, such as ginger from IDR 30,000/kg to IDR 50,000/kg, kencur previously from IDR 35,000/kg to IDR 42,000/kg, temulawak from IDR 4,000/kg to IDR 12,000/kg. The increasing need for medicinal plants has attracted the students of State Junior High School 3 Tawangsari to control the way to market these immune-enhancing medicinal plants and instant herbs digitally (online). The online herbal medicine marketing training is carried out in stages consisting of 1) pre-test related to students' understanding of herbal medicine and online marketing media, 2) digital marketing-based herbal marketing training, and post-test to measure the impact of implementing a successful service program. The training results showed an increase in students' understanding regarding the marketing of herbal medicine online as evidenced by the higher post-test scores than the pre-test. This training has given students a new understanding of the intricacies of digital herbal marketing that can support the Sukoharjo program as the City of Herbal Medicine in Indonesia.